Emotion categorization of body expressions in narrative scenarios - Volkova, Ekaterina P.; Mohler, Betty J.; Dodds, Trevor J.; Tesch, Joachim; Bülthoff, Heinrich H. (Frontiers in Psychology, 2014)
Humans can recognise emotions expressed through body motion with high accuracy even when the stimuli are impoverished. However, most of the research on body motion has relied on exaggerated displays of emotions. In this paper we present two experiments where we investigated whether emotional body expressions could be recognised when they were recorded during natural narration. Our actors were free to use their entire body, face and voice to express emotions, but our resulting visual stimuli used only the upper body motion trajectories in the form of animated stick figures. Observers were asked to perform an emotion recognition task on short motion sequences using a large and balanced set of emotions (amusement, joy, pride, relief, surprise, anger, disgust, fear, sadness, shame and neutral). Even with only upper body motion available, our results show recognition accuracy significantly above chance level and high consistency rates among observers. In our first experiment, that used more classic emotion induction setup, all emotions were well recognised. In the second study that employed narrations, four basic emotion categories (joy, anger, fear and sadness), three non-basic emotion categories (amusement, pride and shame) and the "neutral" category were recognised above chance. Interestingly, especially in the second experiment, observers showed a bias towards anger when recognising the motion sequences for emotions. We discovered that similarities between motion sequences across the emotions along such properties as mean motion speed, number of peaks in the motion trajectory and mean motion span can explain a large percent of the variation in observers' responses. Overall, our results show that upper body motion is informative for emotion recognition in narrative scenarios.